Discursive gaps in the implementation of public health policy guidelines in India: The case of HIV testing - Sheikh, Kabir; Porter, John (Social science & medicine (1982), 2010)
The implementation of standardized policy guidelines for care of diseases of public health importance has emerged as a subject of concern in low and middle-income countries (LMIC) globally. We conducted an empirical research study using the interpretive policy analysis approach to diagnose reasons for gaps in the implementation of national guidelines for HIV testing in Indian hospitals. Forty-six in-depth interviews were conducted with actors involved in policy implementation processes in five states of India, including practitioners, health administrators, policy-planners and donors. We found that actors’ divergences from their putative roles in implementation were underpinned by their inhabitation of discrete ‘systems of meaning’ – frameworks for perceiving policy problems, acting and making decisions. Key gaps in policy implementation included conflicts between different actors’ ideals of performance of core tasks and conformance with policy, and problems in communicating policy ideas across systems of meaning. These ‘discursive’ gaps were compounded by the lack of avenues for intellectual intercourse and by unaccounted interrelationships of power between implementing actors. Our findings demonstrate the importance of thinking beyond short-sighted ideals of aligning frontline practices with global policymakers’ intentions. Recognising the deliberative nature of implementation, and strengthening discourse and communications between involved actors may be critical to the success of public health policies in Indian and comparable LMIC settings. Effective policy implementation in the long term also necessitates enhancing practitioners’ contributions to the policy process, and equipping country public health functionaries to actualize their policy leadership roles.